Curcumin as Adjuvant Therapy in Mild-Moderate Covid 19 - Kartika, Ronald Winardi; Tendean, Marcel; Yong, Bernard Jonathan Christian; Sartika, Katarina Dewi; Suradji, Eka Widrian; Hasan, Irsan (Writing Center IMERI FMUI, 2022)
Background: Coronavirus (Covid-19) has spread rapidly to more than 200 countries, including Indonesia. Adjuvant therapy of Vitamin C, D, Zinc has become beneficial for Covid-19 treatment to improve the immune system, while Curcumin is still not standard therapy. Curcumin can stimulate specific immune cells and can reduce oxidative stress. There is currently no scientific evidence showing that the addition of Curcumin can protect COVID-19, especially as an anti-inflammation and anticoagulant effect. Methods: This cross-sectional study was conducted at Ukrida Hospital from January -June 2021. The inclusion criteria are Mild-Moderate Covid-19 use on Curcumin and Supplement therapy ( Vitamin C, Vitamin D, and zinc). Data analyses with SPSS v.20 use Anova test and Kruskall Walis test. This study had been approved by The Institutional Board of the Faculty of Medicine Universitas Krida Wacana, Indonesia (No. 1053/SLKE-IM/UKKW/FKIK/KE/II/2021). Research Objectives: To see the effect of Curcumin as an additional therapy from Covid-19 by clinical and laboratory inflammation indicators of the usefulness of Curcumin are such as ratio neutrophil/lymphocyte, ratio platelet/lymphocyte, erythrocyte sedimentation rate (ESR), C-Reactive Protein ( CRP), and D Dimer. Results: There were 246 cases, with 62.6% male and 56.5% female taking Curcumin. Curcumin has a good effect in reducing inflammation and coagulation in mild-moderate Covid-19. Patient who got Curcumin or without Curcumin as additional supplement therapy shows patient that got Curcumin has decreased inflammatory markers N/L ratio (p = 0.041), P/L ratio (p = 0.040), ESR (p = 0.013 ), and CRP ( p= 0.045). Curcumin also has an anticoagulant effect that shows a decrease of D-Dimer ( p= 0.020). Conclusion: Curcumin is beneficial in mild-moderate Covid-19 as an anti-inflammatory and anticoagulant.